The Effect of Leisure Time Sport on Executive Functions in Danish 1st Grade Children - Gitte Meilandt Siersbaek; Mona Have; Niels Wedderkopp (MDPI AG, 2022)
Physical inactivity can influence children's executive functions with severe impact on wellbeing and academic learning. The objective is to study the effect of leisure time sport on executive functions in Danish 1st grade children, and secondary to explore if socio-economy is a confounder for associations between leisure time sport and executive functions. This study is a sub-study nested within a cluster-randomized controlled trial with two arms (ClinicalTrials.gov, NCT02488460). 505 children from twelve schools, mean age 7.2 ± 0.3 years participated. Outcomes for executive function were "Modified Eriksen Flanker/Reverse Flanker Task" and "Behavior Rating Inventory of Executive Function" (BRIEF-P). Parents used SMS-tracking to register their children's leisure time sport. Multivariate analyzes was performed using mixed linear regression, with adjustment for highest parental education, sex, municipality, and school-type. We found that leisure time sport seems to significantly improve working memory (WM) with nearly 20%, and furthermore it seems to be a significant predictor of 'Initiate' (the ability to begin an activity, to generate ideas, responses or problem-solving strategies). Socio-economy was not found to be a confounder. This study lends support to the hypothesis that leisure time sport is related to working memory capacity in children.